GADD45: a crucial component of the DNA damage response and a potential cancer therapeutic target - Kirti S. Prabhu (4246144) (2025)
Introduction The Growth Arrest and DNA Damage-Inducible 45 (GADD45) proteins, including GADD45α, GADD45β, and GADD45γ, play a crucial role in the cellular stress response and maintaining genome stability. These proteins are involved in various biological processes, including cell cycle arrest, DNA repair, apoptosis, and senescence, particularly when cells encounter genotoxic stress. Areas covered This review outlines the isoform-specific functions of GADD45 proteins in controlling DNA repair, apoptosis, and stress responses, emphasizing their context-dependent effects on cancer progression. We analyze emerging evidence highlighting their dual roles and discuss the potential of targeting GADD45 pathways in cancer therapy. This review was created through an extensive literature search and critical analysis of peer-reviewed articles obtained from PubMed, Scopus, Web of Science, and Google Scholar databases. The search covered literature published from 1994 to 2024, with a focus on recent studies (2018–2024) that examined molecular mechanisms, clinical correlations, and therapeutic implications of GADD45 signaling. Expert opinion In summary, the GADD45 family serves as a crucial link between stress signaling, genomic stability, and immune regulation. Gaining a clearer understanding of their isoform-specific and context-dependent functions will be vital to fully leverage their potential as biomarkers and therapeutic targets in precision oncology. Plain Language Summary Cells in our body are constantly exposed to stress, such as harmful chemicals, radiation, or inflammation, which can damage their DNA. The GADD45 family of genes (GADD45α, GADD45β, and GADD45γ) helps protecst cells by repairing damaged DNA, halting cell division to facilitate repair, or triggering cell death if the damage is irreparable. These genes act as molecular ‘switches’ that help maintain the health and stability of our genetic material. In many cancers, the normal protective role of GADD45 is disrupted. In some cancers, GADD45 genes act as tumor suppressors, stopping tumor growth, while in others, they may help cancer cells survive by improving their ability to handle stress and resist chemotherapy. This dual role, known as the ‘survival paradox,’ depends on the type of cancer and its molecular context. Understanding how GADD45 functions in different cancers could guide the development of new therapies. Future treatments might target these genes to restore their tumor-suppressive functions or block their stress-protective effects, improving cancer control and treatment response. Other Information Published in: Expert Opinion on Therapeutic Targets License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/14728222.2025.2589807